Diagenetic and metamorphic overprint and deformation history of Permo-Triassic Tethyan sediments, SE Tibet - Dunkl, István; Lin, Ding; Montomoli, Chiara; Wemmer, Klaus; Rantitsch, Gerd; Antolin, Borja; El Bay, Rachida; Appel, Erwin (Himalayan Journal of Sciences, 2008)
DOI = 10.3126/hjs.v5i7.1252 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.